Polish, lithuanians, jewishs, belarrusians community from Vilnius region and Western Belarussia in 1939-1944. Myths and stereotipes. - Burauskaitė, Birutė (Genocidas ir rezistencija, 2004)
This review gives a broader account of the presentations made during the international conference held at the Institute of History of the University of Bialystok, Poland, on 27–27 May 2004. The presentations reveal the attitude of Polish historians towards Lithuania in 1939–1944 and the interests of the Lithuanian national group in the Polish–administered Vilnius region. The other presentations at the conference were mainly based on local historical material collected in the Bialystok region and in the areas of western Belarus administered by Poland until September 1939. These were more ethnographic, sociological, and ethnic studies.
Keywords: Soviet occupation; German occupation; Polish; Jews; belarussians; Vilnius region